2003
DOI: 10.1051/parasite/2003101p65
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of neurocysticercosis patients after treatment using an antigen detection ELISA

Abstract: Summary:Seven patients with active neurocysticercosis (NCC) received an eight days treatment with albendazole and were followed up using computed tomography (CT-scan) and a monoclonal antibody based ELISA for the detection of circulating antigen (Ag-ELISA). Only three patients were cured as was shown by CT-scan and by the disappearance of circulating antigens one month after treatment. After a second course of albendazole therapy, two other patients became seronegative. CT-scan showed the disappearance of viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…Unfortunately, neither CT-scan nor MRI were available in the study area so that the serological results could not be confirmed by brain imaging techniques. Although this implies that the results of this study have to be interpreted with caution, the correlation between living cysts as shown by CT scan and the Ag-ELISA results (Nguekam et al 2003a) is excellent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, neither CT-scan nor MRI were available in the study area so that the serological results could not be confirmed by brain imaging techniques. Although this implies that the results of this study have to be interpreted with caution, the correlation between living cysts as shown by CT scan and the Ag-ELISA results (Nguekam et al 2003a) is excellent.…”
Section: Discussionmentioning
confidence: 99%
“…The Ag-ELISA only detects living cysticerci (Garcia et al 2000;Erhart et al 2002;Nguekam et al 2003b) and rapidly becomes negative when the cysts die after treatment (Nguekam et al 2003a). The Ab-ELISA, on the other hand, detects antibodies against living, degenerating and dead cysticerci and does not allow differentiation between these different kinds of cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Since the levels of antigen drop quickly in cured NCC patients, serum antigen monitoring is of great help in the follow-up of clinical cases. 142,[145][146][147][148][149] Detectable levels of circulating antigen do not always correlate with neurological symptoms. A study in India followed 42 antigen-positive individuals for up to 5 years, and none of them developed neurological symptoms associated with NCC.…”
Section: Advantages and Disadvantages Of Antigen Detection In Cysticementioning
confidence: 99%
“…4 that may guide the clinician as to when withdrawal of antiepileptic medication in patients with epilepsy due to NCC seems justified. In the absence of CT the clinician may attempt to get serial T. solium cysticercosis antigen levels 89 The 'access gap' is caused by factors such as inconsistent access to health facilities with antiepileptic medication, lack of knowledge of affected people and their families, medical personnel and entire communities on the topic of epilepsy, traditional concepts as to the origin of epilepsy and resulting stigma towards people with epilepsy, among other factors. [96][97][98][99] This stigma was clearly demonstrated in a recent study from Zambia which showed that people with epilepsy are disadvantaged regarding social and economic matters compared to people with other chronic diseases without an attached stigma, such as asthma, diabetes mellitus, hypertension, and rheumatic heart disease.…”
Section: Difficulties Of Treating Ncc In Sub-saharan Africamentioning
confidence: 99%
“…An alternative could be the performance of T. solium cysticercosis antigen-ELISA which has been shown to indicate active disease 82 and the course of antigen levels has been suggested as a successful tool to monitor treatment response. 89 In the eastern and southern African region, the T. solium cysticercosis antigen-ELISA has been used for detecting the infection in both pigs and humans. Treatment in the absence of neuroimaging The majority of patients in resource-poor settings have neither access to neuroimaging nor to T. solium cysticercosis antigen ELISA.…”
Section: Difficulties Of Treating Ncc In Sub-saharan Africamentioning
confidence: 99%